Intra-observer and inter-observer agreement of the manual examination of the lumbar spine in chronic low-back pain - Qvistgaard, Etienne (Springer-Verlag, 2006)
Examination is a cornerstone in the manual procedures leading to mobilisation/manipulation of the low back. The observer variation of the more specific segmental tests remains to be investigated. Two skilled specialists in manual medicine examined the segmental changes in the lumbar spine. The patients were unknown to the examiners and no information of the case history was given. All test results were recorded by an observer present in the room who ensured that no conversation was allowed during the examination. The primary outcome measures were the kappa values for each test. The matching was defined as acceptable (acc) within two neighbouring levels and perfect (per) on the same level. Intra-observer variation (tested in 33 patients and 10 subjects without low-back pain): The agreement between first and second segmental diagnosis examination was 70% (per) and 82% (per + acc). Kappa values were: segmental diagnosis 0.60 (per) and 0.70 (per + acc), multifidus test 0.51 (per) and 0.60 (per + acc), sideflexion 0.57 (per) and 0.69 (per + acc), and ventral flexion 0.31 (per) and 0.45 (per + acc). Inter-observer variation (tested in 60 patients): The agreement for segmental diagnosis between the examiner A and B was 42% (per) and 75% (per + acc). Kappa values were: segmental diagnosis 0.21 (per) and 0.57 (acc), multifidus test 0.12 (per) and 0.48 (acc), sideflexion 0.22 (per) and 0.45 (acc), and ventralflexion 0.22 (per) and 0.44 (acc). By manual tests, skilled examiners seem to be able to diagnose segmental dysfunctions in the low back. The clinical implication of these dysfunctions remains to be clarified.